Electrical Stimulation and Conductive Polymers as a Powerful Toolbox for Tailoring Cell Behaviour in vitro - Rocha, Igor; Cerqueira, Gabrielle; Varella Penteado, Felipe; Córdoba de Torresi, Susana I. (Frontiers in Medical Technology, 2021)
Electrical stimulation (ES) is a well-known method for guiding the behaviour of nerve cells in in vitro systems based on the response of these cells to an electric field. From this perspective, understanding how the electrochemical stimulus can be tuned for the design of a desired cell response is of great importance. Most biomedical studies propose the application of electrical potential to cell culture arrays while examining the cell response regarding viability, morphology, and gene expression. Conversely, various studies failed to evaluate how the fine physicochemical properties of the materials used for cell culture influence the observed behaviours. Among the various materials used for culturing cells under ES, conductive polymers (CPs) are widely used either in pristine form or in addition to other polymers. CPs themselves do not possess the optimal surface for cell compatibility due to their hydrophobic nature, which leads to poor protein adhesion and hence poor bioactivity. Therefore, understanding how to tailor the chemical properties on the material surface will determine the obtention of improved ES platforms. Moreover, the structure of the material either in a thin film or in porous electrospun scaffolds also affects the biochemical response and needs to be considered. In this review, we examine how materials based on CPs influence cell behaviour under ES, and we compile the various ES setups and physicochemical properties that affect cell behaviour. This review concerns the culture of various cell types, such as neurons, fibroblasts, osteoblasts, and Schwann cells, and it also covers studies on stem cells prone to ES. To understand the mechanistic behaviour of these devices, we also examine studies presenting a more detailed biomolecular level of interaction. This review aims to guide the design of future ES setups regarding the influence of material properties and electrochemical conditions on the behaviour of in vitro cell studies.